E-Commerce, Self Assessment System, Tax Knowledge and Automatic Exchange of Information on Tax Avoidance Intentions - Novi Rista; Vita Aprilina; Sugeng Baryanto (Jurnal Ilmiah Manajemen dan Bisnis, 2023)
This study aims to examine whether or not there is an effect of E-Commerce, Self Assessment System, Tax Knowledge and Automatic Exchange of Information (AEoI) on the Tax Avoidance Intentions of E-commerce Business Actors. The research method uses a quantitative approach. The data used are primary data by distributing questionnaires in the form of Google forms to e-commerce business people. The research population is e-commerce players in West Java Province as many as 1,820 e-commerce business people. Determination of the sample with the Slovin formula resulted in 100 respondents. The sampling technique is purposive sampling with data analysis using Multiple Linear Regression. The results of this study indicate that Tax Knowledge has a positive effect on intention to avoid tax while E-Commerce, Self Assessment System and Automatic Exchange of Information (AEoI) have no effect on intention to avoid tax.